Aderência a um programa de atividade física e fatores associados - Costa, Bruna Varoto da [UNESP]; Bottcher, Lara Belmudes [UNESP]; Kokubun, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
The aim of this study was to verify the adherence of participants in a program of physical activity; and to verify if there is any association between the age, Body Mass Index and General Functional Fitness Index with this adherence. It was used the control of frequency for 62 months and data of the anthropometric and functional evaluations of 122 participants (58 + 9 years). 49.2% of the participants gave the program up and 50.8% remained to it. The average of permanence time was 24 + 17 months. The percentage of the adherence of people with satisfactory fitness is greater than with not satisfactory fitness. The percentage of adherence of older people is larger than younger age. The percentage of adherence of not-obese is greater than of obese. However, none of these variables presented statistical difference. It can be concluded that even though there was adherence with similar results even to permanence as to desistance, the time of permanence in the program was very high when compared to other studies.

O objetivo desse estudo foi verificar a aderência de participantes em um programa de atividade física e se existe associação da Idade, Índice de Massa Corporal e Índice de Aptidão Funcional com essa aderência. Utilizou-se controle de freqüência por 62 meses e dados das avaliações antropométrica e funcional de 122 participantes (58 + 9 anos). Desses 49,2% desistiram e 50,8% aderiram ao programa. A média de tempo de permanência foi 24 + 17 meses. A porcentagem da aderência de pessoas com aptidão satisfatória é maior do que não satisfatória. A porcentagem de aderência das pessoas mais velhas é maior do que com idades inferiores. A porcentagem de aderência de não obesos é maior que de obesos. Entretanto, nenhuma dessas variáveis apresentou diferença estatisticamente significativa. Conclui-se que embora tenha existido aderência com valores próximos tanto para permanência quanto desistência, o tempo de permanência no programa foi alto quando comparado a outros estudos
Adherence to physical activity program and associated factors
Keywords: Adherence; Physical activity; Survival analysis